Collaboration between Vocational Education and Industry to Enhance The Internship Competence of Students at SMK Negeri 8 Samarinda - Fitrianti, Fitrianti; Haryaka, Usfandi; Dwiyono, Yudo; Azainil, Azainil; Masruhim, Amir; Sudarman, Sudarman (Borneo Educational Journal (Borju), 2025)
This study utilizes a descriptive qualitative method, selected because it allows an in-depth exploration of the collaboration between vocational education and the shipping industry from multiple perspectives. Data collection through interviews, observations, and document analysis provides a comprehensive understanding of the processes, experiences, and challenges involved in enhancing the internship competencies of shipping students at SMK Negeri 8 Samarinda. This approach is well-suited to capturing the complex interactions and dynamic relationships between the school and industry partners in real-world settings. The findings reveal a strong, collaborative framework where school leaders, teachers, and industry representatives work closely to design and implement an internship program that integrates both technical skills and essential soft skills required in maritime careers. The curriculum is regularly updated to align with national and international standards, and students receive preparatory training and certifications to ensure industry readiness. Supervision and mentoring during internships foster the development of skills and professionalism. Importantly, the dual evaluation system involving both the school and industry partners provides ongoing, actionable feedback that supports continuous program improvement. This study uniquely contributes by offering a detailed account of a successful, synergistic collaboration model specifically tailored to vocational maritime education, addressing a gap in prior research that often generalizes education-industry partnerships. It highlights the integration of soft skills within technical training and emphasizes the value of collaborative program evaluation, which together significantly enhance student competence and preparedness for the maritime workforce. By documenting these innovative practices in the Indonesian vocational education context, this research provides valuable insights and a replicable model for other maritime schools aiming to improve internship effectiveness through meaningful industry collaboration